Association of weight loss and weight loss maintenance following diabetes diagnosis by screening and incidence of cardiovascular disease and all‐cause mortality: An observational analysis of the ADDITION‐Europe trial. Issue 3 (21st December 2020) - Strelitz, Jean; Sharp, Stephen J.; Khunti, Kamlesh; Vos, Rimke C.; Rutten, Guy E. H. M.; Webb, David R.; Witte, Daniel R.; Sandbæk, Annelli; Wareham, Nicholas J.; Griffin, Simon J.
Abstract: Aims: Short‐term weight loss may lead to remission of type 2 diabetes but the effect of maintained weight loss on cardiovascular disease (CVD) is unknown. We quantified the associations between changes in weight 5 years following a diagnosis of diabetes, and incident CVD events and mortality up to 10 years after diagnosis. Materials and methods: Observational analysis of the ADDITION‐Europe trial of 2730 adults with screen‐detected type 2 diabetes from the UK, Denmark and the Netherlands. We defined weight change based on the maintenance at 5 years of weight loss achieved during the year after diabetes diagnosis, and as 5‐year overall change in weight. Incident CVD events (n = 229) and all‐cause mortality (n = 225) from 5 to 10 years follow‐up were ascertained from medical records. Results: Gaining >2% weight during the year after diabetes diagnosis was associated with higher hazard of all‐cause mortality versus maintaining weight [hazard ratio (95% confidence interval): 3.18 (1.30‐7.82)]. Losing ≥5% weight 1 year after diagnosis was also associated with mortality, whether or not weight loss was maintained at 5 years: 2.47 (0.99‐6.21) and 2.72 (1.17‐6.30), respectively. Losing ≥10% weight over 5 years was associated with mortality among those with body mass index <30 kg/m 2 [4.62 (1.87‐11.42)]. Associations with CVD incidence were inconclusive. Conclusions: Both weight loss and weight gain after screen‐detected diabetes diagnosis were associated with higher mortality, but not CVD events, particularly among participants without obesity. The clinical implications of weight loss following a diagnosis of diabetes probably depend on its magnitude and timing, and may differ by body mass index status. Personalization of weight loss advice and support may be warranted.